Disposable Versus Reusable Absorbent Underpads for Prevention of Hospital-Acquired Incontinence-Associated Dermatitis and Pressure Injuries. Issue 4 (July 2017) - Francis, Kathleen; Pang, Sau Man; Cohen, Brenda; Salter, Helene; Homel, Peter
Abstract : PURPOSE: The primary purpose of our study was to determine if there is a difference in the occurrence of hospital-acquired pressure injuries (HAPIs) and incontinence-associated dermatitis (IAD) in incontinent adults using a disposable versus reusable absorptive underpads. We also compared hospital length of stay in the 2 groups. DESIGN: Randomized controlled trial using cluster randomization based on inpatient care unit. SUBJECTS AND SETTING: Four hundred sixty-two patients admitted to 4 medical-surgical study units participated in the study; 252 used reusable underpads (control group) and 210 subjects used disposable underpads (intervention group). The study setting was a 711-bed acute care hospital located in Brooklyn, New York. METHODS: Two units were randomly allocated to use disposable incontinence pads, and the remaining 2 units used standard, reusable incontinence pads. Data for PI and IAD occurrences were collected weekly by specially trained RNs (skin care champions) on the assigned units. A 2-level hierarchical linear model was used to analyze the effects of the intervention on primary and secondary outcomes separately from any effects of the unit of randomization. RESULTS: HAPIs were significantly lower in the disposable underpads group: 5% versus 12% ( P = .02). Rates of hospital IAD were not significantly different between the groups ( P = .22). Analysis of a secondary outcome, hospital length of stay, was also lower in patients who used disposable underpads (6 days vs 8 days; P = .02). CONCLUSIONS: Findings suggest that use of disposable incontinence pads reduces HAPI but not IAD occurrences. The effect of disposable, absorbent incontinence pads should be considered when initiating a hospital-wide skin and PI prevention and treatment plan.